Multi‐layered stochasticity and paracrine signal propagation shape the type‐I interferon response - Ulfert Rand; Melanie Rinas; Johannes Schwerk; Gesa Nöhren; Melanie Linnes; Andrea Kröger; Michael Flossdorf; Kristóf Kály‐Kullai; Hansjörg Hauser; Thomas Höfer; Mario Köster (Molecular Systems Biology)
Abstract The cellular recognition of viruses evokes the secretion of type‐I interferons (IFNs) that induce an antiviral protective state. By live‐cell imaging, we show that key steps of virus‐induced signal transduction, IFN‐β expression, and induction of IFN‐stimulated genes (ISGs) are stochastic events in individual cells. The heterogeneity in IFN production is of cellular—and not viral—origin, and temporal unpredictability of IFN‐β expression is largely due to cell‐intrinsic noise generated both upstream and downstream of the activation of nuclear factor‐κB and IFN regulatory factor transcription factors. Subsequent ISG induction occurs as a stochastic all‐or‐nothing switch, where the responding cells are protected against virus replication. Mathematical modelling and experimental validation show that reliable antiviral protection in the face of multi‐layered cellular stochasticity is achieved by paracrine response amplification. Achieving coherent responses through intercellular communication is likely to be a more widely used strategy by mammalian cells to cope with pervasive stochasticity in signalling and gene expression.